Tax Credits for Debt Reduction : A Proposal. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
The incentives for domestic investment in debtor countries are influenced by the terms of their external obligations and by the system of taxation utilized to provide government revenue for debt payments. It is well known that existing debt contracts could be altered to improve the incentives for investment but this has proven difficult to accomplish, perhaps because individual creditors have incentives not to agree to such changes. In this paper we show that a simple tax credit scheme that can be implemented unilaterally by the debtor government can overcome at least some of the inefficiencies caused by existing debt contracts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet